Once vs twice-daily abacavir and lamivudine in African children. (17th July 2016) - Musiime, Victor; Kasirye, Philip; Naidoo-James, Bethany; Nahirya-Ntege, Patricia; Mhute, Tawanda; Cook, Adrian; Mugarura, Lincoln; Munjoma, Marshall; Thoofer, Navdeep K.; Ndashimye, Emmanuel; Nankya, Immaculate; Spyer, Moira J.; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Background: Antiretroviral therapy (ART) adherence is critical for successful HIV treatment outcomes. Once-daily dosing could improve adherence. Plasma concentrations of once-daily vs twice-daily abacavir + lamivudine are bioequivalent in children, but no randomized trial has compared virological outcomes. Methods: Children taking abacavir + lamivudine-containing first-line regimens twice daily for more than 36 weeks in the ARROW trial (NCT02028676, ISRCTN24791884) were randomized to continue twice-daily vs move to once-daily abacavir + lamivudine (open-label). Co-primary outcomes were viral load suppression at week 48 (12% noninferiority margin, measured retrospectively) and lamivudine or abacavir-related grade 3/4 adverse events. Results: Six hundred and sixty-nine children (median 5 years, range 1–16) were randomized to twice daily ( n  = 333) vs once daily ( n  = 336) after median 1.8 years on twice-daily abacavir + lamivudine-containing first-line ART. Children were followed for median 114 weeks. At week 48, 242/331 (73%) twice daily vs 236/330 (72%) once daily had viral load less than 80 copies/ml [difference −1.6% (95% confidence interval −8.4, +5.2%) P  = 0.65]; 79% twice daily vs 78% once daily had viral load less than 400 copies/ml ( P  = 0.76) (week 96 results similar). One grade 3/4 adverse event was judged uncertainly related to abacavir + lamivudine (hepatitis; once daily). At week 48, 9% twice daily vs 10% once daily reported missing one or more ART pills in the last 4 weeks ( P  = 0.74) and 8 vs 8% at week 96 ( P  = 0.90). Carers strongly preferred once-daily dosing. There was no difference between randomized groups in postbaseline drug-resistance mutations or drug-susceptibility; WHO 3/4 events; ART-modifying, grade 3/4 or serious adverse events; CD4% or weight-for-age/height-for-age (all P  > 0.15). Conclusion: Once-daily abacavir + lamivudine was noninferior to twice daily in viral load suppression, with similar resistance, adherence, clinical, immunological and safety outcomes. Abacavir + lamivudine provides the first once-daily nucleoside backbone across childhood that can be used to simplify ART.